2003
DOI: 10.1029/2002jd003030
|View full text |Cite
|
Sign up to set email alerts
|

Improved simulations of snow extent in the second phase of the Atmospheric Model Intercomparison Project (AMIP‐2)

Abstract: [1] Simulations of snow-covered area (SCA) over Northern Hemisphere lands by a suite of general circulation models (GCMs) are evaluated. Results from GCM experiments submitted by an international array of research groups participating in the second phase of the Atmospheric Model Intercomparison Project (AMIP-2) are compared to a data set derived primarily from visible band satellite imagery provided by the United States National Oceanic and Atmospheric Administration. At continental to hemispheric scales we fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 64 publications
3
61
2
Order By: Relevance
“…Significant between-model variability is found in mean NA-SCE, comparable in magnitude to the betweenmodel variability found in AMIP-2 atmospheric GCMs [Frei et al, 2003], and most of the AOGCMs in this study underestimate observed NA-SCE.…”
Section: Discussionmentioning
confidence: 54%
“…Significant between-model variability is found in mean NA-SCE, comparable in magnitude to the betweenmodel variability found in AMIP-2 atmospheric GCMs [Frei et al, 2003], and most of the AOGCMs in this study underestimate observed NA-SCE.…”
Section: Discussionmentioning
confidence: 54%
“…Second, although NOAA data are considered the most accurate and consistent observations of continental-scale SCE (Frei et al, 2003), studies suggest that springtime snow cover may be overestimated in mountainous regions (Déry and Brown, 2007) and Northern Canada (Wang et al, 2005). While absolute SCE may be biased in some regions, validity of multi-year continental-scale trends remains uncertain.…”
Section: Recent Observed and Simulated Springtime Climate Trendsmentioning
confidence: 99%
“…Other possible support for a snow darkening role in model snow cover biases comes from an analysis by Frei et al (2003) of 1979-1995 in SST-forced models. This study found universal high biases in modeled December-March SCE over Eastern Asia and the Tibetan Plateau, two regions we find to be strongly affected by snow darkening (Figs.…”
Section: Recent Observed and Simulated Springtime Climate Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Snow also modulates the hydrologic cycle (Dyer, 2008;Graybeal and Leathers, 2006;Leathers et al, 1998;Todhunter, 2001); influences ecosystem functioning (Jones et al, 2001); and is a significant resource for many mid latitude populations and for populations whose water is derived from mountainous and northerly cold regions (Barnett et al, 2005;Barry et al, 2007). Snow observations are critical for the validation of climate models Frei et al, 2003MacKay et al, 2006;Roesch et al, 1999).…”
Section: Introductionmentioning
confidence: 99%